1995
DOI: 10.1128/jb.177.11.3087-3094.1995
|View full text |Cite
|
Sign up to set email alerts
|

The posttranslational modification of phosphoglucomutase is regulated by galactose induction and glucose repression in Saccharomyces cerevisiae

Abstract: The enzyme phosphoglucomutase functions at a key point in carbohydrate metabolism. In this paper, we show that the synthesis of the major isoform of yeast phosphoglucomutase, encoded by the GAL5 (PGM2) gene, is regulated in a manner that is distinct from that previously described for other enzymes involved in galactose metabolism in the yeast Saccharomyces cerevisiae. Accumulation of this isoform increased four-to sixfold when the culture experienced either glucose depletion or heat shock. However, heat shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
(31 reference statements)
3
25
0
2
Order By: Relevance
“…A strain lacking the minor PGM isoform (pgm1⌬) was previously shown to exhibit a modest (10 -15%) decrease in PGM activity that did not cause any growth defects in Galcontaining media (14,15). Similarly, we found that Ca t levels were comparable when the wild-type and pgm1⌬ strains were grown under these conditions.…”
Section: Lithium Elevates Ca T In Yeast Cells Grown In Media Containisupporting
confidence: 61%
See 2 more Smart Citations
“…A strain lacking the minor PGM isoform (pgm1⌬) was previously shown to exhibit a modest (10 -15%) decrease in PGM activity that did not cause any growth defects in Galcontaining media (14,15). Similarly, we found that Ca t levels were comparable when the wild-type and pgm1⌬ strains were grown under these conditions.…”
Section: Lithium Elevates Ca T In Yeast Cells Grown In Media Containisupporting
confidence: 61%
“…1). Saccharomyces cerevisiae has two PGM genes, PGM1 and PGM2, with the latter accounting for ϳ80 -90% of the total activity (14). At least one of the PGM genes is required for cell growth in media containing Gal, but not Glc, as sole carbon source.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main function of PGM2 (phosphoglucomutase) is the conversion of glucose-1-phosphate to glucose-6-phosphate, but other functions such as involvement in the synthesis of cell wall and cellular calcium ion homeostasis have been reported (6,12). Moreover, conditional posttranscriptional modification of PGM2 has been reported (9,11). This modification is controlled by culture conditions such as heat shock and carbon sources.…”
Section: Tyr112mentioning
confidence: 99%
“…This alternative function could be related to the previous finding that Pgm2p undergoes a post-translational modification in the form of a glucosyl residue attached by a phosphodiester linkage to one or more O-linked mannose residues (46). The extent of the post-translational modification of Pgm2p is regulated by both the carbon source and heat shock; however, it is unclear what role this modification plays in Pgm2p function (47,48). Because cytosolic proteins are not glycosylated in bacteria and because E. coli PGM shares only limited homology (31% sequence identity) with yeast Pgm2p, we asked whether the expression of E. coli PGM can suppress the Ca 2ϩ homeostasis defects associated with the pgm2⌬ mutation.…”
Section: Expression Of E Coli Pgm In the Pgm2⌬mentioning
confidence: 99%